EFFECT OF SACHA INCHI OIL (PLUKENETIA VOLUBILIS) IN THE DIET OF BROILER BREEDERS ON THE PRODUCTIVE PERFORMANCE OF THEIR PROGENY - Lucas L., Juan (2011)
The aim of the study was to evaluate the effect of Sacha inchi oil (Plukenetia volubilis) in the diet of broiler breeders on the productive performance of their progeny. The study included 720 male Cobb Vantres 500 chicks where half of them originated from breeders fed with a diet containing 5% Sacha inchi oil and the other half fed with a diet containing conventional fat. Nine replicates per group were used in the study. Body weight, food intake, mortality, feed conversion index (FCI), European productive efficiency index (PEI),and level of active and passive humoral immunity were evaluated. At 42 days of age, the inclusion of Sacha inchi oil in the diet showed a positive but not significant effect on productive performance, but a significant increase in the level of maternal antibodies against Newcastle disease (p<0.05) and a slight increase of maternal antibodies against Gumboro and infectious bronchitis viruses.